Pediatric low-grade glioma: Targeted therapeutics and clinical trials in the molecular era - Manoharan, Neevika; Liu, Kevin X.; Mueller, Sabine; Haas-Kogan, Daphne A.; Bandopadhayay, Pratiti (Neoplasia (New York, N.Y.), 2023)
•Pediatric low-grade glioma (pLGG) is a MAPK pathway-altered disease with novel therapeutic options.•Clinical trials are vital in translation of targeted agents to influence patient care.•Targeted agents have unknown long-term toxicities and unclear impact on pLGG natural history.•Challenges include rapid clinical trial translation, tumor heterogeneity and need to harmonize molecular profiling techniques. pLGGs are a group of tumors for which the era of molecular diagnostics has truly shifted treatment paradigms and patient care. The discovery that this group of tumors is driven by single-gene alterations/fusions in the MAPK pathway has resulted in relatively rapid translation into targeted therapy options for patients with this often chronic disease. This translation has been facilitated through efforts of multiple collaboratives and consortia and has led to the development of clinical trials testing the role of targeted therapies in pLGG. Although these developments represent promise, many questions remain regarding these therapies including their long-term toxicities and their potential effects on the natural history of pLGG.